From Chud to Merya [Review of: Rahkonen, P. (2013). South-Eastern Contact Area of Finnic Languages in the Light of Onomastics. Jyväskylä: Bookwell Oy] - Irma I. Mullonen (Izdatelstvo Uralskogo Universiteta, 2014)
The article reviews the work by Pauli Rahkonen devoted to the research of substrate Finno-Ugric hydronymy of the Upper Volga region and adjacent territories where there lived Merya, Muroma, Meshchera and Chud — peoples mentioned in old manuscripts. The author emphasizes the contemporary level of the work using a wide range of methods reflecting the experience of both Russian and Finnish schools of onomastics and based upon extensive and mostly reliable data. The work provides a number of new trustworthy etymologies with solid historical phonetic argumentation. The author also gives a positive appraisal of the method based upon the distribution of typical toponymic stems of the Old Mordvinian, Merya, Murom and Meshchera types with meanings ‘upper’ — ‘lower’, ‘big’ — ‘small’, ‘black’ — ‘white’ which were reconstructed based on the established phonetic correlations and the connections of those stems to the corresponding ethnical areas, traced according to manuscripts. P. Rahkonen’s analysis leads to generally reliable conclusions, testifying, among others, to a more Western, in comparison with the contemporary, area of the Old Mordvinians’ settlement as well as to close relations between the Merya and Muromian languages having more connections with the Balto-Fenno-Sami linguistic community than with the Mari one. The author pays close attention to the conclusion about Permic (not Volga) origin of Meshchera confirmed by the Permic phonetic form of typical toponymic stems and by related archaeological data. The author recognizes that, with reference to old hydronyms, P. Rahkonen could reconstruct a chain of languages and dialects linking Balto-Fennic and Volga groups of the Western Uralic languages. However, the author regrets to notice that the abovementioned chain does not include the Ves of Belozerye which had, as to toponymy, non-Balto-Fennic origin. The review also debates some statements related to the non-Balto-Fennic attribution of Chud as well as to the isolation of some hydronymic formants (-bol, -ra) and ...